2019
DOI: 10.1161/circinterventions.119.008307
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Academic Research Consortium High Bleeding Risk Criteria in an All-Comers Registry of Percutaneous Coronary Intervention

Abstract: Background: Recently, the Academic Research Consortium for High Bleeding Risk (ARC-HBR) has been proposed to standardize the definition of HBR, which was arbitrarily defined as a Bleeding Academic Research Consortium 3 or 5 bleeding ≥4% at 1-year. However, the prevalence and the expected bleeding event rate of HBR patients defined by ARC-HBR criteria are currently unknown in the real-world percutaneous coronary intervention practice. Methods: We applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 19 publications
8
82
2
Order By: Relevance
“…14 Similar trends were observed in the CREDO-Kyoto study, in which the 5-year incidence of the primary bleeding endpoint increased with increasing number of ARC-HBR criteria. 24 Conversely, in patients with ACS, prior PAD, and malignancy, it might be better to consider the balance between the risk and benefits of de-escalation of antiplatelet therapy. In addition, this study confirmed that severe CKD, severe anemia, and heart failure are associated with both ischemic and bleeding events, which is consistent with previous studies in which CKD, anemia, and heart failure, among other factors, were found to be common predictors of both thrombotic and bleeding events.…”
Section: Advance Publicationmentioning
confidence: 99%
“…14 Similar trends were observed in the CREDO-Kyoto study, in which the 5-year incidence of the primary bleeding endpoint increased with increasing number of ARC-HBR criteria. 24 Conversely, in patients with ACS, prior PAD, and malignancy, it might be better to consider the balance between the risk and benefits of de-escalation of antiplatelet therapy. In addition, this study confirmed that severe CKD, severe anemia, and heart failure are associated with both ischemic and bleeding events, which is consistent with previous studies in which CKD, anemia, and heart failure, among other factors, were found to be common predictors of both thrombotic and bleeding events.…”
Section: Advance Publicationmentioning
confidence: 99%
“…2,10,11,22 Patients with major bleeding may require discontinuation of antiplatelet therapy or experience haemodynamic changes and adverse effects of transfusion, all of which may lead to increased adverse outcomes such as MI, stroke, stent thrombosis, and death. 7,[22][23][24] However, the inhospital bleeding rate of nonagenarians remains unclear. This study showed that the inhospital major bleeding rate of nonagenarians with AMI undergoing PCI was as high as 15.6% and IABP or PCPS use is associated with this adverse event.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty clinical variables were identified as major or minor criteria by consensus, supported by published evidence, and patients are considered to have HBR if at least one major or two minor criteria are met. A previous study from a Japanese all-comers registry (CREDO-Kyoto Registry Cohort-2) [ 26 ] demonstrated that the prevalence of patients with HBR was 43% and the cumulative incidence of major bleeding in patients in the HBR group was 10.4% at one year after PCI; this is much higher than the prevalence of 4% defined at the proposal of the ARC-HBR criteria. These results suggest that application of the ARC-HBR criteria can identify patients with HBR in Japanese clinical practice despite the different risk profiles for bleeding events between East Asian and Western populations [ 12 , 13 , 15 ].…”
Section: Importance Of Bleeding Risk Assessment In East Asian Patimentioning
confidence: 95%